Assessment of veterinary pharmaceutical warehouse management practices and its associated challenges in four selected zones and Bahir Dar city of Amhara regional state, Ethiopia - Wondie Mekonen, Abibo; Sintayehu, Tadilo; Endeshaw Woldeyohanins, Alem; Tefera Mekasha, Yesuneh; Weldegerima Atsbeha, Berhanemeskel (Frontiers in Veterinary Science, 2024)
A pharmaceutical warehouse is part of the pharmaceutical supply chain and is essential to maintaining the quality and efficacy of veterinary pharmaceuticals for successful animal health service delivery. However, poor storage conditions, improper handling, inappropriate use, and disposal constitute challenges for veterinary supplies in animal health services. Therefore, this study aimed to assess the existing practices and challenges in governmental veterinary clinics and private veterinary drug wholesalers' warehouse management in Ethiopia. A cross-sectional study was conducted on a total of 37 veterinary health facilities found in four selected zones (south Gondar, west Gondar, central Gondar, and west Gojam zones) and in the Bahir Dar administrative city. Zones were selected using a simple random sampling technique. Data was collected using a structured questionnaire, pre-defined and tested observational checklists, and semi-structured interview guides. Descriptive statistics were used to analyze the quantitative data, while qualitative data was analyzed using a thematic approach. The study revealed the presence of poor stock management practices, such as the absence of standard operating procedures for activities in their warehouses, in about 59.5% of facilities. In any of the surveyed facilities, bin cards and system software utilization were unsatisfactory. The absence of disposal guidelines was detected in 83.8% of the facilities, and the practice of timely disposal of expired drugs was also dissatisfactory. Contrary to study findings in governmental veterinary clinics, private veterinary drug wholesalers follow good storage practices (86.25%) in accordance with theoretical recommendations. The storage conditions in governmental clinics were rated poor at 48.3% (> 80%, which is the limit to the acceptable rate for good storage conditions). The challenges of inadequate infrastructure, a lack qualified staff, problems with availability and affordability of pharmaceutical products, insufficient regulatory practice, and budget constraints were mentioned. A holistic approach from related stakeholders should be followed to improve the existing challenges and bring the sector to greater efficiency.